Sleep apnea in school-age children living at high altitude - M. Grimm (Pulmonology, 2023)
Introduction Among adults, sleep apnea is more common in highlanders than in lowlanders. We evaluated the sleep apnea prevalence in children living at high altitude compared to age-matched low-altitude controls.Methods Healthy children, 7-14 y of age, living at 2500-3800m in the Tien Shan mountains, Kyrgyzstan, were prospectively studied in a health post at 3250m. Healthy controls of similar age living at 700-800m were studied in a University Hospital at 760m in Bishkek. Assessments included respiratory sleep studies scored according to pediatric standards, clinical examination, medical history, and the pediatric sleep questionnaire (PSQ, range 0 to 1 with increasing symptoms).Results In children living at high altitude (n = 37, 17 girls, median [quartiles] age 10.8y [9.6;13.0]), sleep studies revealed: mean nocturnal pulse oximetry 90% (89;91), oxygen desaturation index (ODI, >3% dips in pulse oximetry) 4.3/h (2.5;6.7), apnea/hypopnea index (AHI) total 1.7/h (1.0;3.6), central 1.6/h (1.0;3.3), PSQ 0.27 (0.18;0.45). In low-altitude controls (n=41, 17 girls, age 11.6y [9.5;13.0], between-groups comparison of age P=0.69) sleep studies revealed: pulse oximetry 97% (96;97), ODI 0.7/h (0.2;1.2), AHI total 0.4/h (0.1;1.0), central 0.3/h (0.1;0.7), PSQ 0.18 (0.14;0.31); P<0.05, all corresponding between-group comparisons.Conclusions In school-age children living at high altitude, nocturnal oxygen saturation was lower, and the total and central AHI were higher compared to children living at low altitude. The greater score of sleep symptoms in children residing at high altitude suggests a potential clinical relevance of the nocturnal hypoxemia and subtle sleep-related breathing disturbances.